The Compression Behavior of Undisturbed and Compacted Loess Under the Controlling of Total Suction and Injected Solutions - Zhang, Tongwei; Hu, Zhengjin; Lan, Hengxing; Deng, Yongfeng; Zhang, Huyuan (Frontiers in Earth Science, 2022)
Thousands of square kilometers of habitable land have been created on the Loess Plateau in China. In arid and semi-arid area of Northwest China, the mechanical behavior of structural loess is sensitive to water intrusion and human engineering activities. Due to different physical and mechanical properties of natural and compacted loess, the impacts of ambient humidity and saline water migration on their deformation are still unclear. This paper developed an oedometer test to investigate the compression behavior of natural and compacted loess under environmental humidity (represented by total suction Ψ) and injection water salinity (represented by osmotic suction Ψπ) changes. The results showed that the volume changes Δe of compacted loess (the dry density is 1.8 g/m3) under different total suctions (14.01 MPa to 146.23 MPa) and salinities of injected solution (0.17 mol/L NaCl, 0.29 mol/L Na2SO4 and distilled water) were under 0.01. The changes of void ratio for undisturbed loess increased about 8 times with 10 times decreasing of total suction, which is corresponding to the increase of relative humidity (RH). In the stage of solution injection, the deformation of undisturbed loess increased with the Ψ-Ψπ increasing, and the difference under different humidity reached to nearly 20 times. The mechanism was that the salt inside undisturbed loess would deliquescence when the RH was higher than DRH (Deliquescence Relative Humidity), and the natural structure collapsed. The compression index Cc of samples generally decreased with Ψ-Ψπ, and the compressibility of undisturbed loess was higher. The swelling indices Cs of samples also decreased with Ψ-Ψπ, but the variation was not significant. The strain-stress relationships of loess can be well described by Duncan-Chang constitutive model. Interestingly, the difference of initial deformation modulus ΔEs of two loess linearly related to the Ψ-Ψπ, which represented the structural compression under the coupling of total suction and osmotic suction. The Δεmax between the structural loess and compacted loess exponential increased with Ψ-Ψπ. In the engineering practice, the humidity and saline water intrusion should be considered in the long-term behavior of loess in shallow layer.